Pemodelan Kecepatan Arus dan Tinggi Gelombang Pada Rencana Breakwater Kolam Pelabuhan Meulaboh Dengan Menggunakan Program Delft3D - Ichsan Syahputra; Heny Yuliana (Jurnal Teknik Sipil Unaya, 2019)
The Meulaboh port in West Aceh Regency is one of the ports in the west coast of Aceh Province. Initial operation of this port began in 2016 and currently serves crossing activities with the Meulaboh - Sinabang pass. The Meulaboh port is located in open water facing the Indian Ocean. In extreme conditions, ships often have to delay shipping due to high waves that cause shocks to the ship. Based on these problems, the study will provide an overview of the impact and hydrodynamic response of the Meulaboh port pool area and analyze the impact of wave heights on activities in the port pond based on several Breakwater construction layout scenarios. Alternative handling scenarios are carried out using the Delft3D program. The distribution of wave height at the direction of the wind from the Southwest with Hs = 4.908 m, and Ts = 7.254 seconds which shows the dominant wave from the Southwest restrained by Breakwater and the wave height in front of the port mouth ranges from between 0-1 meters so it is safe against activities cruise.